Role of Software Engineering Processes to Develop Environmental Model - Emetere, Moses Eterigho; Akinyemi, Marvel (Journal of Informatics and Mathematical Sciences, 2016)
The recently found systemic errors in atmospheric environmental model are evident inthe malfunctioning of measuring instruments in West Africa. The software development in the past had been compromised; hence the need to embark on new software development is eminent to avoid future environmental accident. The architectural structures of the new model, as well as the financial importance were examined. Therefore, there is the need for writing of detachable source codes to assist the collective software development of environmental models. The architectural structures of the new model, as well as the financial importance were examined. Therefore, there is the need for writing detachable source codes to assist the collective software development of environmental models.